Influence of Geometric Error of Rollers on Rotational Accuracy of Cylindrical Roller Bearings (Xibei Gongye Daxue Xuebao, 2019)
As the rotation of roller bearings is carried out under geometrical constraint of the inner ring, outer ring and multiple rollers, the motion error of the bearing should also be resulted from geometric errors of bearing parts. Therefore, it is crucial to establish the relationship between geometric errors of bearing components and motion error of assembled bearing, which contributes to improve rotational accuracy of assembled bearing in the design and machining of the bearing. For this purpose, considering roundness error and dimension error of the inner raceway, the outer raceway and rollers, a prediction method for rotational accuracy of cylindrical roller bearings is proposed, and the correctness of the proposed prediction method is verified by experimental results. The influences of roller's geometric error distribution, roller's roundness error and the number of rollers on the runout value of inner ring are investigated. The results show that, the roller arrangement with different geometric errors has a significant impact on rotational accuracy of cylindrical roller bearings. The rotational accuracy could be improved remarkably when multiple rollers with different dimension error are distributed alternately according to the size error. Even-order roundness error of rollers has a significant effect on the rotational accuracy, and the decrease level depends on the orders of roundness errors of bearing parts and the number of rollers. But odd-order roundness error of rollers has almost no effect on the rotational accuracy. The rotational accuracy of assembled bearing would be significantly improved or decreased when even order harmonic of rollers and the number of rollers satisfy specific relationships. The greater the order of roundness error of the rollers, the more severe the influence of the roller number on rotational accuracy of assembled bearing. The rotational accuracy can not be always improved with the increase of the number of rollers.